Seasonal and Diurnal Variability of Rain Heights at An Equatorial Station - Abayomi Isiaka Yussuff; Nor Hisham Haji Khamis (Institute of Advanced Engineering and Science, 2015)
Seasonal and diurnal rain heights variation at Universiti Teknologi Malaysia, Johor was studied. Slant path rain attenuation prediction and modeling is crucial to satellite equipment design; a major input is the rain height. One year meteorological ground-based, S-band, 3D RAPIC precipitation radar data at 500m resolution sourced from the Malaysian Meteorological Department was complemented with two-year TRMM PR data sourced from JAXA Earth Observation Research Center. After filtering, sorting, extraction and decoding of the data, vertical reflectivity profiles were constructed; from which rain height parameters were extracted. TRMM PR processed monthly (3A25) and daily (2A23) rainfall precipitation data were similarly used to obtain rain height parameters to investigate the seasonal and diurnal variations. Results from this work suggested that rain height parameters are influenced by both seasonal and diurnal variations. Higher seasonal variability was observed during south-west and pre-southwest monsoons. Rain heights were also observed to be higher in the night than in the day time.